Second Generation Biodiesel Production from Upgrading of Palm-Based Bio-Oil: Technology Study through Process Simulation - Maharani Dewi Solikhah; Hanafi Prida Putra; Adi Prismantoko; Agus Kismanto; Galuh Wirama Murti; Tetsuya Araki; Hiroshi Nabetani (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Biodiesel has become favorable fuel for diesel fuel substitute to overcome the limited fossil fuel resources while facing the increasing of energy consumption. However, the use of FAME biodiesel is currently limited to mixing up to 30%. Therefore, it is necessary to consider other fuels as an alternative to diesel oil. One of them is by developing second generation biodiesel, which produced from the upgrading process of bio-oil as a result of pyrolysis. Bio-oil can be upgraded to fuel with range naphtha through two main processes that consisted of hydro-processing and catalytic cracking. Techno-economic studies on bio-oil production from oil palm biomass have been studied but the techno-economic studies up to upgraded bio-oil have not included. Before a techno-economic study was carried out, it was necessary to select the process technology route of upgrading bio-oil. Therefore, it is required to conduct a study of industry and the comparison of second generation biodiesel production technology from the upgrading of oil palm-based bio-oil to obtain an optimum process flow diagram. Process simulations were conducted using ChemCad software so that the mass balance and ratio of energy consumption was obtained. This work estimated the biofuel produced from palm residues collected from 19 units of a 60 tons/hour palm oil mill. The bio-oil input is 70.35 tons/hours with upgrading oil yield of 32.21%. The energy yield of this model is 35.7% while required 76.5 MMJ/hour of the energy. The energy required for this process can be provided by an integrated fuel upgrading facilities that connected with the palm bio-oil production plant could provide self-sustainable production facilities.